2012
DOI: 10.1177/0020764012443751
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative analysis of influences on recovery following a first episode of psychosis

Abstract: Results suggest the importance of assistance with engagement in valued activities and relationships, and provision of messages of worth and hope for recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
70
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(80 citation statements)
references
References 33 publications
6
70
0
Order By: Relevance
“…The mean age of participants ranged from 21 to 28 years old. Most of the studies reviewed reported the durations since participants' attended first episode care services (Bourdeau et al, ; Windell et al, ; Windell & Norman, ), and/or durations of treatment (Eisenstadt et al, ; Norman et al, ; Romano, ). Two studies stated that the duration of illness of the participants were up to 5 years (Windell et al, ; Woodside et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The mean age of participants ranged from 21 to 28 years old. Most of the studies reviewed reported the durations since participants' attended first episode care services (Bourdeau et al, ; Windell et al, ; Windell & Norman, ), and/or durations of treatment (Eisenstadt et al, ; Norman et al, ; Romano, ). Two studies stated that the duration of illness of the participants were up to 5 years (Windell et al, ; Woodside et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…PTG was the key conceptual framework describing positive change following psychosis in only two articles . In many of the remaining articles, PTG following FEP was described by the authors as a part of the recovery process ( n = 7) . Both articles which used PTG as a key concept also drew on the recovery paradigm .…”
Section: Collating Summarizing and Reporting The Resultsmentioning
confidence: 99%
“…Taken together, a range of experiences related to PTG were reported by the participants in the included qualitative studies. An important theme among service users was that their FEP motivated them to develop positive character traits such as greater empathy, maturity and resilience . This theme is reflected in the words of one participant who noted, ‘If I hadn't had this experience then I would have never learnt how to deal with stress’ .…”
Section: Collating Summarizing and Reporting The Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These symptomatic characteristics may contribute to an individual's withdrawal from meaningful activities. Participation in diverse and meaningful activities provides opportunities for social connectedness (Sörgaard et al, 2001) and contributes to wellbeing and recovery (Lai et al, 2013;Windell & Norman, 2012). Wong and Solomon developed a model of community integration that is divided into four factors (i.e., psychological integration, physical integration, social integration, and independence; Gulcur, Tsemberis, Stefancic, & Greenwood, 2008;Wong & Solomon, 2002).…”
Section: Introductionmentioning
confidence: 99%